Phosphorus requirements of tambaqui juveniles - Sousa, Thalles José Rego de; Bomfim, Marcos Antonio Delmondes; Lanna, Eduardo Arruda Teixeira; Ribeiro, Felipe Barbosa; Siqueira, Jefferson Costa de; Silva, Janayra Cardoso; Marchão, Rafael Silva (Semina: Ciências Agrárias, 2018)
The aim of this study was to determine the requirement of digestible phosphorus in diets for juvenile tambaqui (Colossoma macropomum). 300 juveniles (26.4 Â± 0.68 g) were used in a completely randomized design, consisting of six treatments with five replicates and 10 fish per experimental unit. The treatments consisted of six isoprotein, isonitrogenous, and isocalcium rations, with different levels of digestible phosphorus: 0.27; 0.46; 0.67; 0.91; 1.04; and 1.14%. The fish were kept in 30 polyethylene tanks (500 L) with a closed water circulation system and fed six meals per day for 49 days. Parameters of performance and feed efficiency, daily protein, and fat, ash, and phosphorus deposition rates were evaluated. The elevation of digestible phosphorus provided a quadratic increase in feed consumption to a level of 0.92%, linear increase in the consumption of digestible phosphorus, and quadratic reduction in the efficiency of digestible phosphorus for weight gain. The linear response plateau model was the best fit for weight gain and specific growth rate, estimated at 0.55% and 0.56% digestible phosphorus, respectively. The feed conversion and protein efficiency for weight gain improved quadratically up to an estimated level of 0.84% of digestible phosphorus. Body fat deposition improved quadratically up to an estimated level of 0.90% of digestible phosphorus. The linear response plateau model was the best fit for body deposition of protein, ash, and phosphorus, estimated at 0.55%, 0.46%, and 0.59% of digestible phosphorus, respectively. To optimize weight gain, the recommended level of digestible phosphorus in diets for juvenile tambaqui is 0.55%, which corresponds to an estimated level of 0.87% of total phosphorus.